Pengaruh Profitabilitas, Leverage, dan Kebijakan Dividen Terhadap Harga Saham Perusahaan Sektor Energi Tahun 2020-2024 - Athiyya Umareta Nadhir; Erna Sulistyowati (Forum Kerjasama Pendidikan Tinggi, 2026)
This research was conducted because the stock prices of energy companies on the Indonesia Stock Exchange (IDX) often fluctuate erratically, especially with the issue of energy transition and unstable global economic conditions between 2020 and 2024. This research aims to examine the actual influence of Profitability (ROA), Leverage (DER), and Dividend Policy (DPR) on stock prices in the sector. Using quantitative methods and purposive sampling techniques, data was collected from 15 energy companies as samples. After testing using panel data regression, the most suitable model was the Random Effect Model (REM). The results showed that only Profitability (ROA) had a positive and significant influence on stock prices (p = 0.0000). This means that investors in the energy sector prioritize the company's ability to generate profits as a primary consideration. On the other hand, Leverage (DER) with a p value of 0.6862 and Dividend Policy (DPR) with a p value of 0.1807 did not significantly influence stock prices. Overall, the variables in this study only explained 21.72% of stock price movements (Adjusted R-Squared), with the remainder influenced by factors outside the study. These findings are expected to provide insights for investors to focus more on the real profitability of energy companies rather than simply looking at debt levels or dividend distributions.